Foreign direct investments under political uncertainty : a case study of crop production in Ukraine - Valdenfeldt, Anastasiia (SLU/Dept. of Economics, 2013)
Intense competition among companies and luck or unavailability of certain resources in country of company’s origin force last to cross the borders, and start to hunt for new markets and cheaper inputs. However, by investing abroad the company is not only facing and dealing with cultural differences and new regulatory framework, but also becomes dependent on decisions and actions of different and to large extend unknown government. Moreover, the majority of the investments’ flows are directed to developing countries, where power and capabilities of state authorities are considered to be more extensive than in countries of developed economies. The aim of this study is to investigate whether the presence of the political uncertainty in the host country have an impact on final investment decision. The study also describes how by using the means of capital budgeting, the value of political risk could be integrated into financial evaluation of an investment project.